The 5-HT2A Receptor Antagonist M100907 Produces Antiparkinsonian Effects and Decreases Striatal Glutamate - Ansah, Twum; Ferguson, Marcus; Nayyar, Tultul (Frontiers in Systems Neuroscience, 2011)
5-HT plays a regulatory role in voluntary movements of the basal ganglia and have a major impact on disorders of the basal ganglia such as Parkinson’s disease (PD). Clinical studies have suggested that 5-HT2 receptor antagonists may be useful in the treatment of the motor symptoms of PD. We hypothesized that 5-HT2A receptor antagonists may restore motor function by regulating glutamatergic activity in the striatum. Mice treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) exhibited decreased performance on the beam-walking apparatus. Peripheral administration of the 5-HT2A receptor antagonist M100907 improved performance of MPTP-treated mice on the beam-walking apparatus. In vivo microdialysis revealed an increase in striatal extracellular glutamate in MPTP-treated mice and local perfusion of M100907 into the dorsal striatum significantly decreased extracellular glutamate levels in saline and MPTP-treated mice. Our studies suggest that blockade of 5-HT2A receptors may represent a novel therapeutic target for the motor symptoms of Parkinson’s disease.